A super-high thermal conductivity cubic boron nitride-based thermally conductive pad and a preparation method thereof

By reasonably preparing cubic boron nitride and metal oxides, ultra-high thermal conductivity cubic boron nitride-based thermal conductivity gaskets are prepared, which solves the problems of insufficient flexibility and chemical stability of existing thermal conductivity and high thermal conductivity and Good flexible thermal gasket.

CN117089207BActive Publication Date: 2025-02-18SHANGHAI ALLIED PLASTIC IND

Patent Information

Application Number
CN202310651382.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-02-18
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

While meeting the high thermal conductivity requirements, existing thermal conductivity silicone sheets have insufficient flexibility and chemical stability, making it difficult to effectively add cubic boron nitride crystals to improve thermal conductivity.

Method used

By reasonably preparing cubic boron nitride powder, metal oxide powder, metal nitride powder and modifier, an ultra-high thermal conductivity cubic boron nitride-based thermal conductivity gasket was prepared. The method includes mixing cubic boron nitride powder with a modifier, combining metal oxide and metal nitride powder, and treating it with additives such as vinyl silicone oil and crosslinking agents to form high thermal conductivity and good flexibility thermal conductivity with high thermal conductivity and good flexibility Spacing.

Benefits of technology

The thermal conductivity is achieved above 18W/(m·K), and high flexibility and chemical stability are maintained, which is suitable for thermal management of high-power electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004268288460000081
    Figure BDA0004268288460000081
  • Figure HDA0004268288470000011
    Figure HDA0004268288470000011
  • Figure HDA0004268288470000012
    Figure HDA0004268288470000012
Patent Text Reader

Abstract

The present invention relates to the field of thermal conductive material technology, in particular to the field of IPC C08K3, and more specifically to an ultra-high thermal conductive cubic boron nitride-based thermally conductive gasket and a preparation method thereof. In parts by weight, the raw materials for preparing the gasket include: 35-150 parts of cubic boron nitride powder, 30-105 parts of metal oxide powder, 15-40 parts of metal nitride powder, 0.2-0.6 parts of modifier, 2-8 parts of vinyl silicone oil, 0.1-0.8 parts of cross-linking agent, 0.1-0.9 parts of inhibitor, and 0.2-1 parts of catalyst. The modifier includes octyl trimethoxy silane and hexamethyl disilazane, and the weight ratio of octyl trimethoxy silane and hexamethyl disilazane is 1: (0.2-2), which can improve the dispersion performance between various fillers in the system, while controlling the hardness shore 00 to about 20, and the thermal conductivity reaches 18W (m·K) or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive materials, in particular to the field of IPC C08K3, and more specifically to an ultra-high thermal conductive cubic boron nitride-based thermal conductive gasket and a preparation method thereof. Background Art

[0002] With the development of industrial production and science and technology, thermally conductive silicone sheets, as a high-performance thermal conductive interface material, are used to fill the gap between the heating device and the heat sink or metal base, which can form a good thermal conduction path. At the same time, they also play the role of insulation, shock absorption, sealing, etc., and are the most popular materials in electronic products and electronic equipment. However, with the continuous updating and upgrading of electronic products, the power consumption of equipment continues to increase, and the heat generation also increases accordingly. The market's requirements for the thermal conductivity of thermally conductive silicone sheets are also getting higher and higher. Cubic boron nitride (c-BN) is a synthetic superhard material. Its atomic structure is similar to the carbon atom structure in diamond, so it has the characteristics of high density. Cubic boron nitride has a crystal structure similar to that of diamond, and the lattice coefficients of the two are similar. Cubic boron nitride has good thermal conductivity, and its thermal conductivity is 79.54W / m·K, which is much higher than that of ceramic materials. However, due to the high chemical inertness of cubic boron nitride, it has high chemical stability to acids and alkalis in neutral and reducing gas media, and it is difficult to dissolve in resin, and it is not possible to prepare a thermal interface material with good performance. Therefore, under the premise of ensuring compressibility and resilience, finding a method to better add cubic boron nitride crystals into the thermal conductive gasket to improve its thermal conductivity is an urgent problem to be solved.

[0003] CN 112457673 A discloses a high thermal conductivity insulating silicone gasket, wherein the thermal conductive filler is composed of at least one of nano aluminum nitride, cubic boron nitride, and nano silicon carbide and spherical aluminum oxide modified by dodecamethyltrimethoxysilane. The invention makes the product have excellent properties such as high thermal conductivity, high insulation and chemical stability through the modification and compounding design of the filler. CN 112457673 A discloses a high thermal conductivity insulating silicone gasket, wherein the thermal conductive filler is composed of at least one of nano aluminum nitride, cubic boron nitride, and nano silicon carbide and spherical aluminum oxide modified by dodecamethyltrimethoxysilane, but the thermal conductivity of the above gaskets does not exceed 15W / (m·K), and the flexibility is poor (Shore 00 is higher than 40).

[0004] CN 113322037 B discloses a high thermal conductivity epoxy potting glue with thermal shock resistance and a preparation method thereof. Soft boron nitride is added as a second phase to absorb energy when the material is subjected to external force, and at the same time induces the formation of micro cracks, hinders the expansion of cracks, causes crack arrest and improves the toughness of the material; the layered micron boron nitride overlaps each other, and is easy to form a heat conduction channel for phonon transmission, which can effectively improve the thermal conductivity of the epoxy potting glue while meeting the heat dissipation requirements of the potting glue; CN 109880297 A discloses a thermally conductive insulating epoxy resin composite material and a preparation method thereof, wherein a hexagonal boron nitride / gold nanoparticle composite and modified cubic boron nitride micropowder are used as thermal conductive fillers, but due to the compatibility problem between the hexagonal boron nitride and epoxy resin, the percentage of boron nitride added is too low, and the thermal conductivity does not exceed 2W / (m·K). Summary of the invention

[0005] The first aspect of the present invention provides an ultra-high thermal conductivity cubic boron nitride-based thermal conductive gasket. The raw materials for preparing the gasket include, by weight: 35-150 parts of cubic boron nitride powder, 30-105 parts of metal oxide powder, 15-40 parts of metal nitride powder, 0.2-0.6 parts of modifier, 2-8 parts of vinyl silicone oil, 0.1-0.8 parts of cross-linking agent, 0.1-0.9 parts of inhibitor, and 0.2-1 parts of catalyst.

[0006] The particle size of the cubic boron nitride powder is 5-180 μm.

[0007] Preferably, the cubic boron nitride powder includes two types with particle sizes of 5-50 μm and 80-180 μm.

[0008] Preferably, the weight ratio of the cubic boron nitride with a particle size of 5-50 μm and 80-180 μm is 1:(2-5).

[0009] Further preferably, the weight ratio of the cubic boron nitride with a particle size of 5-50 μm to that of 80-180 μm is 1:2.5.

[0010] Further preferably, the cubic boron nitride has a particle size of 5-10 μm and is purchased from Yingkou Liaobin Fine Chemical Co., Ltd., model: BN-C.

[0011] The cubic boron nitride has a particle size of 37-45 μm, model: CBN-810, and is purchased from Funike Superhard Materials Co., Ltd.

[0012] The cubic boron nitride has a particle size of 125-150 μm, model: CBN-850, and is purchased from Funike Superhard Materials Co., Ltd.

[0013] The applicant has found that the modifier includes octyltrimethoxysilane and hexamethyldisilazane, and the weight ratio of octyltrimethoxysilane to hexamethyldisilazane is 1: (0.2-2). On the basis of obtaining good flexibility, the thermal conductivity of the gasket is improved. Cubic boron nitride has high chemical inertness and high chemical stability in the system of the present invention, but poor dispersion performance with resins and various fillers. In the process of exploring the influence of different substances in the components on the dispersion performance of cubic boron nitride, the applicant accidentally found that octyltrimethoxysilane and hexamethyldisilazane compounded in a specific ratio effectively improved the thermal conductivity of the gasket. It may be that there are several active surfaces in cubic boron nitride, which makes hexamethyldisilazane easier to disperse with cubic boron nitride, and octyltrimethoxysilane has better wettability with metal oxide powders and metal nitride powders in the system. The two specific modifiers play a bridging role in different molecular structures, increasing the amount of cubic boron nitride added while improving the wettability with silicone resin.

[0014] The modifier includes octyltrimethoxysilane and hexamethyldisilazane, and the weight ratio of the octyltrimethoxysilane to the hexamethyldisilazane is 1:(0.2-2).

[0015] Preferably, the modifier includes octyltrimethoxysilane and hexamethyldisilazane, and the weight ratio of octyltrimethoxysilane to hexamethyldisilazane is 1:0.8.

[0016] The metal oxide powder includes at least two of spherical aluminum oxide, single crystal aluminum oxide, magnesium oxide, and zinc oxide.

[0017] Preferably, the metal oxide powder includes spherical alumina, single crystal alumina and zinc oxide, and the weight ratio of the spherical alumina, single crystal alumina and zinc oxide is 1:(0.5-2):(0.2-0.5).

[0018] Further preferably, the metal oxide powder includes spherical alumina, single crystal alumina and zinc oxide, and the weight ratio of the spherical alumina, single crystal alumina and zinc oxide is 1:1:0.5.

[0019] Preferably, the spherical alumina particle size is 1-70 μm.

[0020] Further preferably, the spherical alumina has a particle size of 10 μm and is purchased from Shijiazhuang Jinghuang Technology Co., Ltd.

[0021] Preferably, the single crystal alumina particle size is 0.3-5 μm.

[0022] Further preferably, the single crystal alumina has a particle size of 1 μm and is purchased from Dongguan Dongchao New Material Technology Co., Ltd.

[0023] Preferably, the particle size of the zinc oxide is 0.5-3 μm.

[0024] Further preferably, the zinc oxide has a particle size of 1 μm and is purchased from Shanghai Pantian Powder Material Co., Ltd., model: PT-ZnO.

[0025] Preferably, the metal nitride powder comprises aluminum nitride, and the particle size of the aluminum nitride is 2-150 μm.

[0026] Preferably, the aluminum nitride particle size is 50-120 μm.

[0027] Further preferably, the aluminum nitride has a particle size of 70 μm and is purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model: XT-ALN-10.

[0028] The weight ratio of the cubic boron nitride powder, the metal oxide powder and the metal nitride powder is (1.5-6):(1.7-3.5):1.

[0029] Preferably, the weight ratio of the cubic boron nitride powder, the metal oxide powder, and the metal nitride powder is (50-100): (3-6).

[0030] Preferably, the weight ratio of the cubic boron nitride powder to the vinyl silicone oil is 20:1.

[0031] The vinyl content in the vinyl silicone oil is 0.08-2.6%.

[0032] Preferably, the vinyl silicone oil includes single-ended vinyl silicone oil, the vinyl content of the vinyl silicone oil is 0.18%, purchased from Guangdong Chensi New Material Technology Co., Ltd., model: CX-352M.

[0033] The cross-linking agent includes at least one of terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil, and terminal-side hydrogen-containing silicone oil.

[0034] Preferably, the cross-linking agent includes end-side hydrogen-containing silicone oil purchased from Guangdong Chensi New Material Technology Co., Ltd., model: CX350T.

[0035] The catalyst includes a platinum catalyst.

[0036] The platinum catalyst was purchased from Beiteli Polymer Materials Co., Ltd., model: CSAT-F1.

[0037] The inhibitor comprises at least one of methylbutynol, acetylene cyclohexanol and polyvinyl compounds.

[0038] Preferably, the inhibitor comprises acetylene cyclohexanol (CAS: 78-27-3).

[0039] A second aspect of the present invention provides a method for preparing an ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket, comprising the following steps:

[0040] S1, mixing cubic boron nitride powder and a part of a modifier uniformly to obtain a mixture 1;

[0041] S2, mixing metal oxide powder, metal nitride powder and remaining modifier to obtain mixture 2;

[0042] S3, adding vinyl silicone oil and mixture 2 into a container, stirring evenly, to obtain mixture 3;

[0043] S4, adding mixture 1 to mixture 3, stirring evenly, and then adding a cross-linking agent, an inhibitor and a catalyst, stirring evenly, to obtain mixture 4;

[0044] S5, kneading the mixture 4 into a ball shape, and putting it into a vacuum box for vacuum treatment 2-4 times, unloading, calendering, and baking to obtain.

[0045] Preferably, the method for preparing the ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket comprises the following steps:

[0046] S1, mixing cubic boron nitride powder and part of the modifier evenly (stirring at 10-200 rpm for 0.5-90 min) to obtain a mixture 1;

[0047] S2, mixing the metal oxide powder, the metal nitride powder and the remaining modifier evenly (stirring at 150-500 rpm for 0.5-30 min), and baking in an oven at 50-170° C. for 0.5-24 h to obtain a mixture 2;

[0048] S3, adding vinyl silicone oil and mixture 2 into a container, stirring evenly (stirring at 20-50 rpm for 5-30 min) to obtain mixture 3;

[0049] S4, adding mixture 1 to mixture 3, heating to 120-140° C., stirring evenly (stirring at 30-50 rpm for 1-10 min), cooling to room temperature, adding a crosslinking agent, an inhibitor and a catalyst, stirring evenly (stirring at 5-20 rpm for 10-120 min), and turning on vacuum during stirring to obtain mixture 4;

[0050] S5, knead the mixture 4 into a ball shape, put it into a vacuum box for vacuum treatment 3 times, discharge it, roll it (the thickness can be controlled at 0.3-5mm), and bake it (120℃, baking for 15-90min), and then obtain it.

[0051] Beneficial effects:

[0052] 1. The cubic boron nitride powder has two particle sizes of 5-50 μm and 80-180 μm. The weight ratio of the cubic boron nitride with particle sizes of 5-50 μm and 80-180 μm is 1:2.5, which can effectively improve the wettability of cubic boron nitride with vinyl silicone oil, thereby improving the thermal conductivity of the gasket.

[0053] 2. The metal oxide powder includes spherical alumina, single crystal alumina and zinc oxide, and the weight ratio of the spherical alumina, single crystal alumina and zinc oxide is 1:(0.5-2):(0.2-0.5), which can balance the thermal conductivity and flexibility of the gasket.

[0054] 3. The weight ratio of the cubic boron nitride powder and the vinyl silicone oil is (50-100): (3-6), which can improve the high temperature aging performance of the gasket.

[0055] 4. The modifier includes octyltrimethoxysilane and hexamethyldisilazane, and the weight ratio of octyltrimethoxysilane to hexamethyldisilazane is 1:(0.2-2), which can improve the dispersion performance between various fillers in the system, control the hardness shore 00 at about 20, and the thermal conductivity reaches more than 18W (m·K), and its compression rate can also be maintained at 15%. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a graph showing the change in thermal conductivity of the gasket of Example 1 after aging. The curves from top to bottom are high temperature test (125°C), high temperature and high humidity test (85°C & 85% rh), and temperature cycle aging test (-40°C ~ 85°C).

[0057] Figure 2 This is a graph showing the hardness change of the gasket of Example 1 after aging. The curves from top to bottom are high temperature test (125°C), high temperature and high humidity test (85°C & 85% rh), and temperature cycle aging test (-40°C ~ 85°C). DETAILED DESCRIPTION

[0058] Example 1

[0059] A super-high thermal conductivity cubic boron nitride-based thermally conductive gasket. The raw materials for preparing the gasket are, by weight: 80 parts of cubic boron nitride powder, 65 parts of metal oxide powder, 25 parts of metal nitride powder, 0.43 parts of modifier, 4 parts of vinyl silicone oil, 0.2 parts of cross-linking agent, 0.1 parts of inhibitor, and 0.5 parts of catalyst.

[0060] The cubic boron nitride powder has two particle sizes of 5-50 μm and 80-180 μm.

[0061] The weight ratio of the cubic boron nitride with a particle size of 5-50 μm and 80-180 μm is 1:2.5.

[0062] The cubic boron nitride with a particle size of 5-50 μm is of two types: particle size 5-10 μm and particle size 37-45 μm, with a weight ratio of 1:1. The cubic boron nitride has a particle size of 5-10 μm and is purchased from Yingkou Liaobin Fine Chemical Co., Ltd., model: BN-C; the cubic boron nitride has a particle size of 37-45 μm, model: CBN-810, and is purchased from Funike Superhard Materials Co., Ltd.

[0063] The metal oxide powder is spherical alumina, single crystal alumina and zinc oxide, and the weight ratio of the spherical alumina, single crystal alumina and zinc oxide is 1:1:0.5.

[0064] The spherical alumina has a particle size of 10 μm and is purchased from Shijiazhuang Jinghuang Technology Co., Ltd.

[0065] The single crystal alumina has a particle size of 1 μm and is purchased from Dongguan Dongchao New Material Technology Co., Ltd.

[0066] The zinc oxide has a particle size of 1 μm and is purchased from Shanghai Pantian Powder Material Co., Ltd., model: PT-ZnO.

[0067] The metal nitride powder is aluminum nitride with a particle size of 70 μm, purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model: XT-ALN-10.

[0068] The vinyl silicone oil is a single-ended vinyl silicone oil, the vinyl content of the vinyl silicone oil is 0.18%, and it is purchased from Guangdong Chensi New Material Technology Co., Ltd., model: CX-352M.

[0069] The cross-linking agent is end-side hydrogen-containing silicone oil purchased from Guangdong Chensi New Material Technology Co., Ltd., model: CX350T.

[0070] The modifier is octyltrimethoxysilane and hexamethyldisilazane, and the weight ratio of octyltrimethoxysilane to hexamethyldisilazane is 1:0.8.

[0071] The catalyst is a platinum catalyst purchased from Beiteli Polymer Materials Co., Ltd., model: CSAT-F1.

[0072] The inhibitor is acetylene cyclohexanol (CAS: 78-27-3).

[0073] A method for preparing an ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket comprises the following steps:

[0074] S1, mixing cubic boron nitride powder and 0.2 parts of modifier evenly (stirring at 50 rpm for 10 min) to obtain mixture 1;

[0075] S2, mixing metal oxide powder, metal nitride powder and 0.23 parts of modifier evenly (stirring at 200 rpm for 10 min), and baking in an oven at 150° C. for 2 h to obtain mixture 2;

[0076] S3, adding vinyl silicone oil and mixture 2 into a container, stirring evenly (stirring at 20 rpm for 5 min) to obtain mixture 3;

[0077] S4, adding mixture 1 to mixture 3, heating to 130°C, stirring evenly (stirring at 20 rpm for 5 min), cooling to 25°C, adding a crosslinking agent, an inhibitor and a catalyst, stirring evenly (stirring at 10 rpm for 20 min), turning on a vacuum (-0.1 MPa) during stirring, and obtaining mixture 4;

[0078] S5, knead the mixture 4 into a ball shape, and put it into a vacuum box for vacuuming (-0.1 MPa, 60 min) for 3 times, unload, roll (thickness 1 mm), and bake (120° C., baking 90 min) to obtain.

[0079] Example 2

[0080] The specific implementation is the same as Example 1; the difference is that in Example 2: 65 parts of cubic boron nitride powder, 52 parts of metal oxide powder, 21 parts of metal nitride powder, and 0.33 parts of modifier.

[0081] Comparative Example 1

[0082] The specific implementation is the same as Example 1; the difference is that in Comparative Example 1: no modifier is included in the preparation raw materials.

[0083] A method for preparing an ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket comprises the following steps:

[0084] S1, heating vinyl silicone oil, metal oxide powder, metal nitride powder and cubic boron nitride powder to 130°C, stirring evenly (stirring at 20 rpm for 60 min), cooling to 25°C, adding crosslinking agent, inhibitor and catalyst, stirring evenly (stirring at 10 rpm for 30 min), and turning on vacuum (-0.1 MPa) during stirring to obtain mixture 1;

[0085] S2, knead the mixture 1 into a ball, and put it into a vacuum box for vacuuming (-0.1MPa, 60min) for 3 times, unload, roll (the thickness can be controlled at 1mm), bake (120℃, bake for 90min), and obtain.

[0086] Comparative Example 2

[0087] The specific implementation is the same as in Example 1; the difference is that in Comparative Example 2:

[0088] A method for preparing an ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket comprises the following steps:

[0089] S1, vinyl silicone oil, metal oxide powder, metal nitride powder, cubic boron nitride powder, and modifier are stirred evenly (stirring at 20 rpm for 60 min), and then a cross-linking agent, an inhibitor, and a catalyst are added and stirred evenly (stirring at 10 rpm for 30 min). During the stirring, vacuum is turned on (-0.1 MPa) to obtain a mixture 1;

[0090] S2, knead the mixture 1 into a ball, and put it into a vacuum box for vacuuming (-0.1MPa, 60min) for 3 times, unload, roll (the thickness can be controlled at 1mm), bake (120℃, bake for 90min), and obtain.

[0091] Comparative Example 3

[0092] The specific implementation is the same as Example 1; the difference is that in Comparative Example 3: the modifier is vinyl trimethoxy silane and octyl trimethoxy silane, and the weight ratio of the vinyl trimethoxy silane to the octyl trimethoxy silane is 0.8:1.

[0093] Comparative Example 4

[0094] The specific implementation is the same as Example 1; the difference is that in Comparative Example 4: the weight ratio of octyltrimethoxysilane to hexamethyldisilazane is 2:1.

[0095] Performance Testing Methods

[0096] The embodiments and comparative examples were tested for performance.

[0097] Thermal conductivity: measured according to standard ASTM D 5470-17 using Taiwan Ruiling LW-9389 interface material thermal resistance and thermal conductivity measuring device (at 25°C). The test data are listed in Table 1.

[0098] Hardness: measured using shore 00 hardness tester (at 25° C.) according to standard ASTM D2240. The gasket obtained in comparative example 3 is not formed, and the test result is represented by “-”. The test data are listed in Table 1.

[0099] Aging performance test: Example 1 was tested using GFG-400-15 according to standard GB / T2423. Figure 1 , 2 As shown, the tests are: temperature cycle aging test (-40℃~85℃), high temperature and high humidity test (85℃&85%rh), high temperature test (125℃), test time 1000h, and the test data are listed in Table 2.

[0100] Performance test data

[0101] Table 1

[0102] Thermal conductivity (W (m·K)) Hardness (Shore 00) Example 1 18.4 20 Example 2 16.2 20 Comparative Example 1 16.8 78 Comparative Example 2 15.5 40 Comparative Example 3 16.0 50 Comparative Example 4 17.5 45

[0103] Table 2

[0104]

Claims

1. An ultra-high thermal conductivity cubic boron nitride-based thermally conductive pad, characterized in that: The raw materials for preparing the gasket are, by weight: 35-150 parts of cubic boron nitride powder, 30-105 parts of metal oxide powder, 15-40 parts of metal nitride powder, 0.2-0.6 parts of modifier, 2-8 parts of vinyl silicone oil, 0.1-0.8 parts of cross-linking agent, 0.1-0.9 parts of inhibitor, and 0.2-1 parts of catalyst; The modifier is octyltrimethoxysilane and hexamethyldisilazane, and the weight ratio of octyltrimethoxysilane to hexamethyldisilazane is 1:0.8; The cubic boron nitride powder has two types of particle sizes: 5-50 μm and 80-180 μm, and the weight ratio of the cubic boron nitride with particle sizes of 5-50 μm and 80-180 μm is 1:2.5; The metal oxide powder is spherical alumina, single crystal alumina and zinc oxide, and the weight ratio of the spherical alumina, single crystal alumina and zinc oxide is 1:1:0.

5.

2. The ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket according to claim 1, characterized in that: The weight ratio of the cubic boron nitride powder, the metal oxide powder and the metal nitride powder is (1.5-6):(1.7-3.5):

1.

3. The ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket according to claim 2, characterized in that: The weight ratio of the cubic boron nitride powder to the vinyl silicone oil is (50-100):(3-6).

4. The ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket according to claim 1, characterized in that: The cross-linking agent includes at least one of terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil, and terminal-side hydrogen-containing silicone oil.

5. A method for preparing the ultra-high thermal conductivity cubic boron nitride-based thermally conductive gasket according to claim 1, characterized in that: The following steps are involved: S1, mixing cubic boron nitride powder and 0.2 parts of a modifier evenly to obtain a mixture 1; S2, mixing metal oxide powder, metal nitride powder and remaining modifier to obtain mixture 2; S3, adding vinyl silicone oil and mixture 2 into a container, stirring evenly, to obtain mixture 3; S4, adding mixture 1 to mixture 3, stirring evenly, and then adding a cross-linking agent, an inhibitor and a catalyst, stirring evenly, to obtain mixture 4; S5, kneading the mixture 4 into a ball shape, and putting it into a vacuum box for vacuum treatment 2-4 times, unloading, calendering, and baking to obtain.

Citation Information

Patent Citations

  • Thermal-conducting and insulating epoxy resin composite material and preparation method thereof

    CN109880297A

  • A thermally shock resistant, high thermal conductivity epoxy potting compound and its preparation method

    CN113322037B

  • High-thermal-conductivity insulating silica gel gasket and preparation method thereof

    CN112457673A

  • Thermally conductive silicone composition

    EP0896031A2

Cited By

  • Boron nitride-based heat-conducting gasket, preparation method and application

    CN121652593A